The Politeness Levels of Thanking and Apologizing: A Corpus Linguistic Investigation Across Generations in the Movies - Ari Muhammad Syifa; Dasril Davidra; Almira Fidela Artha (Unipdu Jombang, 2023)
The levels of politeness in expressing thanking and apologizing connect to the concept of language attitude within sociolinguistics. Language attitude in sociolinguistics refers to an individual’s mental disposition or feelings towards a particular language. It implies that a person's language attitude can range from being favorable, and indifferent, to unfavorable influenced by the environment. Based on the corpus linguistics, this study aimed to investigate politeness levels of thanking and apologizing in American movies across generations, from Baby Boom to Alpha Generation using a corpus software, AntConc, as a tool to process the necessary data. The result of this study showed that the levels of politeness thanking, and apologizing had different choices of words in the movies of each generation. In addition, this was due to factors such as environment and knowledge of the rules of expressions such as Thanks or Thank you, and Sorry or Pardon. Thus, speakers of every generation tend or rarely use those expressions because they want or unwanted to use the word, and they choose to use it. For future study, perhaps it is recommended to explore American cartoons as the object, psycholinguistics approach, and language educational concentration.